Ab Initio Study of Strain Effects on the Quasiparticle Bands and Effective Masses in Silicon - Mohammed Bouhassoune; Arno Schindlmayr (Advances in Condensed Matter Physics)
Using ab initio computational methods, we study the structural and electronic properties of strained silicon, which has emerged as a promising technology to improve the performance of silicon-based metal-oxide-semiconductor field-effect transistors. In particular, higher electron mobilities are observed in n-doped samples with monoclinic strain along the [110] direction, and experimental evidence relates this to changes in the effective mass as well as the scattering rates. To assess the relative importance of these two factors, we combine density-functional theory in the local-density approximation with the GW approximation for the electronic self-energy and investigate the effect of uniaxial and biaxial strains along the [110] direction on the structural and electronic properties of Si. Longitudinal and transverse components of the electron effective mass as a function of the strain are derived from fits to the quasiparticle band structure and a diagonalization of the full effective-mass tensor. The changes in the effective masses and the energy splitting of the conduction-band valleys for uniaxial and biaxial strains as well as their impact on the electron mobility are analyzed. The self-energy corrections within GW lead to band gaps in excellent agreement with experimental measurements and slightly larger effective masses than in the local-density approximation.